¿Antifascismo o ferrerada?: la izquierda francesa y el octubre español de 1934 - Hugo García (Mélanges de la Casa de Velázquez, 2012)
This article, which is based on a broader study of 1930s anti-fascism, analyses the impact in France of the insurrection in Spain in 1934, from a standpoint somewhere between a cultural history of politics and a history of collective action. It recounts the political, social and discursive aspects of the mobilisation of the French left in defence of the insurgents, highlighting continuities from earlier events like the Ferrer case of 1909 and the particularities of the nascent anti-fascist movement which led the protest (and which this helped to build). It draws on newspaper records and on documentation from archives in Spain (AGA, Fundación Pablo Iglesias) and France (Archivos de la Prefectura de Policía de París, Archivos de la Ligue des Droits de l’Homme) to present a fresh view of the organisation and activities of the principal committees involved in the movement—particularly the Groupe des amis de l’Espagne y el Comité populaire d’aide à toutes les victimes du fascisme en Espagne.